2014
DOI: 10.1039/c4ta01350f
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Ta2O5–ZnO films as cathodic buffer layers in inverted polymer solar cells

Abstract: Ta2O5–ZnO composite films with varied composition were fabricated by sol–gel processing and applied as cathodic buffer layers (CBLs) for inverted polymer solar cells, and demonstrated enhanced power conversion efficiency with excellent stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…It is also observed that the O iii and O ii peaks are negatively shied when the sputter-etching increases, which is mostly due to the electronic interaction between the out-diffused Al atoms and PMMA polymer. 60 The variation of O 1s bonding states as function of sputter-etching times are in good agreement with the existence of rich AlO x layer and V O in the interfacial regime (Fig. 6b).…”
Section: Filament Growth Processes In Pmma-based Devicessupporting
confidence: 78%
“…It is also observed that the O iii and O ii peaks are negatively shied when the sputter-etching increases, which is mostly due to the electronic interaction between the out-diffused Al atoms and PMMA polymer. 60 The variation of O 1s bonding states as function of sputter-etching times are in good agreement with the existence of rich AlO x layer and V O in the interfacial regime (Fig. 6b).…”
Section: Filament Growth Processes In Pmma-based Devicessupporting
confidence: 78%
“…Residing at the D-A interface, the charge-transfer (CT) state mediates the charge carrier separation and the free charge carrier recombination, and its properties directly affect the device performance, especially the open-circuit voltage (V OC ) 15 17 . Furthermore, degradation paths are rather complex and differ between standard and inverted stack architectures 18 21 . For example, Krebs et al .…”
Section: Introductionmentioning
confidence: 99%
“…Tantalum silicate glass with high refractive index is expected to offer an exciting new opportunity for enhancing the characteristics of optical components, with more possibilities than many other multi‐component host glass candidates with active luminescent ions . The presence of tantalum ions in silicate glasses also modifies their physical properties to a large extent, including their thermal properties, chemical stability, dielectric constant, and luminescence intensity, which widens the range of the applications such as arrayed‐waveguide grating, dynamic random access memory (DRAM) devices, antireflection coating layers, gas sensors, photocatalysts, solar cells, and optical fibers . Inspired by the superior properties of tantalum‐doped glasses, a few reports have been dedicated to studying the structure of bulk glass based on infrared and Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%